Asamblea en el aula de Filosofía del Derecho - Bardazano, Gianella (2011)
The education of lawyers at UDELAR privileges the transmission of a represented and stabilized knowledge produce by nineteenth-century methodological schools criteria. Some of the principles that characterize University could be adopted as one of the teaching strategies that allow students and teachers to reconsider the fundamental role of general theory of law and legal philosophy in the education of future lawyers. The article describes the potential of the assembly as a teaching practice that may favor or encourage the epistemic rupture with the dogmatic point of view.